SCHOOL ENVIRONMENT INFLUENCE OF STUDENT MOTIVATION SMP NEGERI 1 KECAMATAN PANTAI CERMIN KABUPATEN SOLOK - HARDIANTO, ORI; Drs. Dasrizal, MP, Drs. Dasrizal, MP; SE, M.Si, Nefilinda (STKIP PGRI Sumbar, 2014)
ABSTRACTThe purpose of this study is 1) determine the effect of school facilities and infrastructure to the students motivation SMP Negeri I Kecamatan Pantai Cermin Kabupaten Solok, 2) determine the effect of the presence of a canteen on student motivation SMP Negeri I Kecamatan Pantai Cermin Kabupaten Solok, 3) determine the effect of a school friend of the students motivation SMP Negeri I Kecamatan Pantai Cermin Kabupaten Solok, and 4) determine the effect of school facilities and infrastructure, school canteens and school friends together on student motivation SMP Negeri I Kecamatan Pantai Cermin Kabupaten Solok.The study took place in SMP Negeri I Kecamatan Pantai Cermin Kabupaten Solok. Population of 489 students. With a proportional random sampling technique by 74 students from 489 students in SMP Negeri I Kecamatan Pantai Cermin Kabupaten Solok.The results of the study of environmental influences on students motivation Schools SMP Negeri 1 Kecamatan Pantai Cermin Kabupaten Solok resulted in the following findings: for the effect of school facilities and infrastructure to motivation, t count> t table, is 2.505> 1.99394 and a significance value 0.015 <Î± 0.05. This suggests that school facilities (X1) and a significant positive effect on motivation (Y) students. So the first hypothesis in this study received, to the effect on motivation canteen, t count> t table, is 3.604> 1.99394 and a significance value 0.001 <Î± 0.05. This suggests that the canteen (X2) significant and positive impact on the motivation (Y) So that students first hypothesis in this study received, to the effect on the motivation of school friends t count> t table, is 2584> 1.99394 and a significance value 0.012 <Î± 0.05. This suggests that the school friends (X3) significant and positive impact on the motivation (Y) so that the students in this study the first hypothesis is accepted, to the influence of school facilities, canteen and, school friends together on the motivation of F count is 14.607 with a significance value is 0.000> 0.05. This suggests that the independent variables, school facilities (XI), cafeteria (X2), and school friends (X3) together (simultaneously) can explain the motivational influence on the dependent variable (Y).